2022
DOI: 10.3389/fpsyg.2022.855749
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of behavior change techniques used to promote physical activity among women in midlife

Abstract: Women in midlife experience health risks that could be mitigated by regular physical activity and reduced sedentary time, but this population rarely achieves physical activity levels that would protect their health. As a result, many behavioral interventions are designed to promote physical activity in this population, which are purportedly guided by theoretical models of health behavior (change) and activate an associated set of behavior change techniques (BCTs). The efficacy and effectiveness of these interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 108 publications
2
10
0
Order By: Relevance
“…In addition, this method runs the risk of including BCTs that do not add to effectiveness but happened to be included in the effective interventions [ 89 ]. Furthermore, although other evaluation methods such as meta-analyses can provide generalizable conclusions [ 89 ], poor quality in intervention description and high heterogeneity in the designs may not allow for statistical analysis of the effectiveness of individual BCTs or a combination of BCTs on the intervention outcomes [ 21 , 44 , 78 , 91 , 92 ]. Making confident estimates of the effectiveness of BCTs and BCT combinations for a given behavior delivered in a particular way in a given setting to a given target population requires synthesis of information from diverse sources [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this method runs the risk of including BCTs that do not add to effectiveness but happened to be included in the effective interventions [ 89 ]. Furthermore, although other evaluation methods such as meta-analyses can provide generalizable conclusions [ 89 ], poor quality in intervention description and high heterogeneity in the designs may not allow for statistical analysis of the effectiveness of individual BCTs or a combination of BCTs on the intervention outcomes [ 21 , 44 , 78 , 91 , 92 ]. Making confident estimates of the effectiveness of BCTs and BCT combinations for a given behavior delivered in a particular way in a given setting to a given target population requires synthesis of information from diverse sources [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCIs are typically complex and involve many interacting components and, therefore, a theoretical understanding of how the intervention causes behavior change is needed to strengthen the effects of BCI on clinical outcomes [ 20 ]. A recent scoping review [ 21 ] identified limitations in describing PA interventions in midlife women, with only 59% of the 51 studies specifying an underlying theoretical model. Many studies provided a limited description of how behavior change techniques (BCTs) were activated to achieve desired outcomes and provided limited insight into how the BCTs were received by midlife women [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consuming healthy dietary patterns—with adequate amounts of key nutrients such as protein, calcium, vitamin D, fiber, and fluid intake—might aid in diminishing the degenerative alterations that occur during aging, such as cognitive decline or loss of skeletal muscle [ 21 , 22 ]. Increased physical activity (PA) and reduced sedentary time also contribute to the prevention of chronic diseases throughout the lifespan [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many multi-component lifestyle interventions have been developed to promote healthy aging behaviors for older adults or to reduce the risk of developing complications from existing health conditions, such as stroke [ 23 , 24 , 25 , 26 ]. This is particularly relevant for community-dwelling adults who face the changes associated with aging and who aim to live independently for as long as possible [ 27 ].…”
Section: Introductionmentioning
confidence: 99%